Adat and Sharia in the Ammatoa Community: Family Law, Gender, and Environmental Ethics as Arenas for Educational Negotiations - Nuryamin, Nuryamin; Ahmad, La Ode Ismail; Tenri Padang, Andi; Fatmal, Abd. Bashir; Yusdar, Windi Pratiwi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the negotiation between custom and sharia in the realm of family law as a central arena for educational, ethical, and cultural transformation in the Ammatoa Kajang indigenous community in Bulukumba, South Sulawesi. The study uses qualitative methods, with a framework of educational anthropology and legal anthropology. Data were collected through in-depth interviews, literature studies, and participant observation. In-depth interviews with Ammatoa, academics, community elders, married couples, and family members, while the literature reviewed included journal articles, books, and Islamic law texts. The findings indicate that the Ammatoa Kajang community formally recognizes the normative authority of Islamic law, although it is interpreted selectively through customary-based cultural mechanisms. The principles of Islamic law regarding marriage, inheritance, family obligations, women's roles and gender relations, and social ethics are adapted into symbolic and ritual forms that align with the local cosmology and moral teachings of Pasang ri Kajang. In this context, family law becomes a pedagogical space where Islamic values ​​are not only taught normatively but also realized collectively through rituals, symbolic communication, communal sanctions, and patterns of social interaction. Furthermore, environmental ethics and ecological education in the Ammatoa community are also very prominent, evidenced by their harmony with nature and commitment to preserving it. This study shows that anthropologically, there is an interaction between custom and sharia in the Ammatoa Kajang traditional community in education and law, reflecting a model of Islamic legal education rooted in culture and religion through a process of negotiation, adaptation, and reinterpretation.